Skupna zemljišča v Sloveniji - Petek, Franci (Geografski vestnik, 2007)
This article examines communally-owned land as a historical and social phenomenon, and especially as a significant part of the rural landscape. The introduction, which presents terminology and historical development, is followed by the main part of the article, with information on the situation following Slovenia's independence and the adoption of denationalization laws. It focuses on three aspects of common land: farming associations, denationalized common land, and agriculturally active common land. These are presented at the level of physical geographical units, providing insight into spatial characteristics connected with natural conditions. A concrete example of agriculturally active common land is the alpine pasture Velika Planina, which shows the relationship between grazing-rights holders to the pasture and their expectations regarding future development.
Keywords: kulturna pokrajina; podeželje; rural area; kmetijska zemljišča; raba tal; agrarne skupnosti; planinski pašniki; Velika planina